Kecemasan Tokoh Utama Dalam Novel Canthing Karya Narko Sodrun Budiman Kajian Teori Psikologi Sastra Sigmund Freud - Reza Utmi Agustina; Octo Dendy Andriyanto (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to understand the form of anxiety of the character Kodar Santika in the novel Canthing by Narko Sodrun Budiman. Anxiety is a form of conflict that occurs within oneself. The inner conflict that causes anxiety in Kodar's character comes from an imbalance in the personality structure of the id, ego and superego. Anxiety was Freud's focus. The theory used in this research is Sigmud Freud's theory which focuses on Kodar's anxiety. Anxiety is a feeling of insecurity that develops when someone is faced with a danger that threatens their life because this feeling of insecurity causes anxiety. The method used in this research is a qualitative descriptive method. The data collection techniques used in this research are library study techniques, critical reading techniques, and note-taking techniques. The method used to analyze data is descriptive analysis techniques. Based on the research results, it was found that the main character's anxiety is neurotical anxiety, including fear and confusion. Anxiety is a realistic fear of objects and situations. And the ultimate moralistic fear includes regret and feelings of guilt. The anxiety experienced by Kodar's character is influenced by the economy, temptation towards women, and lack of support from the family. The anxiety felt by Kodar's character can be ended by using ego defense mechanisms in the form of denial, distraction, sublimation, rationalization.